(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explores the etymological characteristics of Latin borrowings in modern English, shedding light on the linguistic evolution that has shaped the vocabulary of the English language. Through a meticulous examination of literature and linguistic data, this study aims to uncover patterns and trends in the adoption and adaptation of Latin words, providing insights into the dynamic nature of language over time.